Liquid absorbing transparent sheet, and wound-covering material containing the sheet
A transparent wound dressing using core-sheath fibers with controlled polymer composition ensures visibility and effective liquid absorption, addressing the challenge of applying dressings without direct visual confirmation.
Patent Information
- Application Number
- JP2023092496
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-05
- Publication Date
- 2024-12-17
AI Technical Summary
Existing wound dressings lack transparency before liquid absorption, making it difficult to apply while confirming the wound position and leading to waste due to failed applications.
A liquid-absorbing transparent sheet made of core-sheath fibers with a hydrophilic polymer outer layer and acrylonitrile-based polymer inner layer, controlled by weight proportion and basis weight, ensuring transparency and high liquid absorption capacity.
The sheet allows wound observation before and after liquid absorption, reducing reapplication errors and waste, while maintaining excellent liquid absorption properties.
Smart Images

Figure 2024174595000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a liquid-absorbent transparent sheet and a wound dressing containing said sheet. [Background technology]
[0002] As the name suggests, wound dressings are sanitary materials that are placed to cover the surface of wounds (wound surfaces) such as burns, abrasions, and bedsores, and serve the roles of protecting the wound surface, preventing it from drying (moisturizing), absorbing exudate (absorbency), and inhibiting bacterial infection. Compared to the conventional mainstream method of covering the wound surface with gauze and disinfecting it with a disinfectant, wound dressings maintain a moist state on the wound surface, which does not inhibit cell activation and allows the wound to heal effectively, and various wound dressings have been reported to date.
[0003] For example, Patent Document 1 reports a water-swellable polymer gel formed from an esterified carboxyl group-containing polysaccharide and a compound having two or more α-amino groups derived from natural amino acids, and Patent Document 2 reports a laminated sheet-like structure in which two or more layers of fiber sheets containing carboxymethylcellulose long fibers in which the carboxymethyl groups are partially protonated are laminated, and the sheets are heat-welded between each other with a thermoplastic resin sheet. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 4044291 [Patent Document 2] JP 2021-172014 A Summary of the Invention [Problem to be solved by the invention]
[0005] Incidentally, in recent years, in addition to moisture retention and liquid absorption, there are cases where transparency is required for wound dressings. This is to meet the demand for observing the healing process from outside the dressing when healing a wound using the wound dressing. Furthermore, if the transparency is manifested before liquid absorption, the wound dressing can be applied while checking the position of the wound, which can reduce the effort of reapplication and the waste of preparing another unused product due to failure in application. The water-swellable polymer gel described in Patent Document 1 and the laminated sheet-like structure described in Patent Document 2 both have excellent transparency and the wound can be observed from outside the dressing, but the transparency is manifested when liquid is absorbed, so they are not suitable for application in which the position of the wound is checked while being applied.
[0006] The present invention has been made in consideration of the problems of the prior art as described above. That is, the present invention aims to provide a sheet-like article that, in an absorbent sheet made of core-sheath fibers composed of an outer layer containing a hydrophilic polymer and an inner layer containing an acrylonitrile-based polymer, can obtain excellent absorbency while exhibiting transparency before absorbing liquid by controlling the flatness of the cross section of the core-sheath fibers, the weight ratio of the fibers in the absorbent sheet, and the basis weight of the absorbent sheet. [Means for solving the problem]
[0007] The present invention has the following configuration. (1) A liquid-absorbent transparent sheet comprising a liquid-absorbent sheath-core fiber composed of an outer layer containing a hydrophilic polymer and an inner layer containing an acrylonitrile-based polymer, the flatness of the core-sheath fiber being 1.10 to 4.50, and the basis weight of the liquid-absorbent transparent sheet being 25 to 180 g / m 2 and the content of the core-sheath fibers in the liquid-absorbent transparent sheet is 25 to 100% by weight. (2) The liquid-absorbent transparent sheet according to (1), characterized in that the liquid-absorbent transparent sheet has a liquid absorption ratio of 1.8 to 15 times. (3) A wound dressing material, comprising the liquid-absorbent transparent sheet according to (1) or (2). (4) The wound dressing material according to (3), further comprising a breathable film. (5) A wound dressing according to (4), characterized in that the breathable film is a urethane film or a silicone film. Effect of the Invention
[0008] The liquid-absorbent transparent sheet of the present invention is suitable for use as a wound dressing, particularly when observing the healing process of a wound, because it has both liquid absorption and transparency. In addition, the transparency of the sheet is exhibited even before liquid absorption, so that the wound dressing can be applied while checking the position of the wound, and the labor required for reapplication and the waste of preparing another unused sheet due to failure in application can be reduced. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, an embodiment of the present invention will be described in detail.
[0010] The lower limit of the mixture ratio of the absorbent core-sheath fibers in the absorbent transparent sheet of the present invention is preferably 25% by weight, more preferably 50% by weight. If the mixture ratio is less than 25% by weight, the transparency and absorbency of the absorbent sheet become insufficient. There is no particular upper limit, but the upper limit theoretically does not exceed 100% by weight, and from the viewpoint of the processability of the sheet and the shape retention after absorbing liquid, the upper limit is preferably 80% by weight.
[0011] The minimum basis weight of the liquid-absorbent transparent sheet is 25 g / m 2 It is preferable that the thickness is 50 g / m 2 More preferably, the weight is 25 g / m 2 If the sheet is less than this value, the liquid absorbency of the sheet will be insufficient. 2 It is preferable that the thickness is 150 g / m 2 It is more preferable that the weight per unit area is 180 g / m 2 If it exceeds this value, the transparency becomes insufficient, and there is a risk that the visibility of the wound area will decrease.
[0012] The absorbent sheath-core fiber used in the present invention is composed of an outer layer containing a hydrophilic polymer and an inner layer containing an acrylonitrile polymer. Specific examples of such absorbent sheath-core fibers include an absorbent layer having a salt-type carboxyl group on the surface obtained by hydrolyzing the surface of an acrylonitrile fiber, a polyacrylonitrile absorbent fiber having a sheath-core structure with an acrylonitrile fiber part remaining in the center, and a crosslinked polyacrylonitrile absorbent fiber having a sheath-core structure obtained by introducing a crosslinked structure by covalent bonding into such an absorbent fiber.
[0013] In particular, the above-mentioned crosslinked polyacrylonitrile-based liquid-absorbent fibers are more preferred because the acrylonitrile-based fiber portion remains in the center, resulting in high physical strength and good handleability during processing, and because there is little change in the length direction of the fiber when it swells, resulting in good dimensional stability of the product.
[0014] The introduction of a crosslinked structure by a covalent bond in such a polyacrylonitrile-based absorbent fiber may be performed before, simultaneously with, or after the hydrolysis of the above-mentioned fiber surface. In addition, the nitrile group of the acrylonitrile-based fiber or the carboxyl group generated by hydrolysis can be used to introduce the crosslinked structure. However, in the method using the carboxyl group generated by hydrolysis, the gel strength of the gel part generated on the fiber surface by hydrolysis is weak, and problems such as the gel falling off at the stage before the introduction of the crosslinked structure or the flowing out of a part of the carboxyl group-containing polymer that has not been crosslinked are likely to occur. In contrast, if a crosslinked structure is introduced using a nitrile group before or during hydrolysis, the gel strength after hydrolysis is high and the amount of the carboxyl group-containing polymer that has not been crosslinked is reduced, which is advantageous in terms of industrial handling and environmental impact. For this reason, the method of introducing a crosslinked structure using a nitrile group before or during hydrolysis is preferable.
[0015] The method for producing a crosslinked polyacrylonitrile-based liquid-absorbing fiber in which a crosslinked structure is introduced by utilizing a nitrile group will be described in detail below. First, the acrylonitrile polymer constituting the raw acrylonitrile-based fiber is preferably a polymer containing 80% by weight or more, preferably 85% by weight or more, of acrylonitrile. Examples of copolymerization monomers include vinyl halides and vinylidene halides such as vinyl chloride, vinyl bromide, and vinylidene chloride; ethylenically unsaturated carboxylic acids and their salts such as acrylic acid, methacrylic acid, maleic acid, and itaconic acid; (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, and butyl (meth)acrylate; vinyl esters such as vinyl acetate and vinyl propionate; ethylenically unsaturated sulfonic acids and their salts such as vinyl sulfonic acid, (meth)allyl sulfonic acid, and p-styrene sulfonic acid; and vinyl compounds such as (meth)acrylamide, vinylidene cyanide, and methacrylonitrile.
[0016] Here, the molecular weight of the acrylonitrile polymer may be that of a molecular weight used as a general clothing fiber or a high molecular weight used as a high strength fiber, but since it is cost-effective to use a general-purpose clothing fiber, it is preferable to use one having a weight average molecular weight of 200,000 or less.
[0017] Next, a method for obtaining absorbent fibers having a desired absorption capacity by using the acrylonitrile fibers as a starting material and introducing a crosslinking structure using nitrile groups will be described in detail. Examples of such a method include a method in which a crosslinking treatment using nitrile groups is followed by a hydrolysis treatment, and a method in which crosslinking and hydrolysis are simultaneously performed using nitrile groups.
[0018] First, a method of performing a hydrolysis treatment after a crosslinking treatment using a nitrile group will be described. As a method of introducing a crosslinking structure using a nitrile group into an acrylonitrile-based fiber, a means of treating the fiber in an aqueous solution having a crosslinking agent concentration of 0.1 to 10.0% by weight at a temperature of 50 to 120°C for 5 to 150 minutes is industrially preferred. If the crosslinking agent concentration or treatment temperature falls below the lower limit, the amount of crosslinking structure introduced by covalent bonds will be insufficient, and conversely, if the crosslinking agent concentration or treatment temperature exceeds the upper limit, the amount of crosslinking structure introduced by covalent bonds will be too large, and in either case, it is difficult to obtain an absorbent fiber that falls within the range of the absorption capacity of the present invention.
[0019] The crosslinking agent is not particularly limited as long as it is a polyfunctional compound having two or more functional groups in one molecule that can chemically react with a nitrile group to form a covalent bond, and examples of the crosslinking agent include polyfunctional compounds having two or more functional groups such as amino groups, epoxy groups, etc. Specific examples include hydrazine hydrate, hydrazine sulfate, hydrazine hydrochloride, hydrazine nitrate, hydrazine bromate, diaminoethane, guanidine carbonate, 1,3-diaminopropane, ethylene glycol diglycidyl ether, etc.
[0020] The method for hydrolyzing the crosslinked acrylonitrile fiber thus obtained is preferably to prepare a fiber to which an alkaline metal compound or an aqueous solution thereof is attached so that the amount of the alkaline metal compound is within the range of 2.5 to 10.0 mmol / g, preferably 5.0 to 10.0 mmol / g, based on the dry weight of the fiber, and to heat the fiber at a temperature of 80° C. or higher for 5 to 180 minutes, preferably for 10 to 120 minutes in a moist heat atmosphere at 100 to 150° C. In this hydrolysis treatment, a crosslinking agent may be added as necessary, or a method of simultaneously treating crosslinking and hydrolysis as described below may be directly adopted.
[0021] The alkaline metal compound used here refers to a substance that shows a pH of 7.5 or more when its 1.0 wt % aqueous solution is formed, and examples of such substances include hydroxides of alkali metals such as Na, K, Li, etc., and alkali metal salts of organic acids such as carbonic acid, acetic acid, formic acid, etc., such as Na, K, Li, etc. Note that, although water is industrially preferred as a solvent for preparing an aqueous solution of an alkaline metal compound, a mixed solvent of water and a water-miscible organic solvent such as alcohol, acetone, dimethylformamide, etc. may also be used.
[0022] Next, a method of simultaneously carrying out crosslinking and hydrolysis using nitrile groups will be described. It is desirable to adopt a method of preparing fibers to which an aqueous solution in which a crosslinking agent and an alkaline metal compound are coexisted is attached so that the amount of the alkaline metal compound is within the range of 2.5 to 10.0 mmol / g, preferably 5.0 to 10.0 mmol / g, and the amount of the crosslinking agent is within the range of 0.1 to 1.5% by weight, preferably 0.5 to 1.0% by weight, based on the dry weight of the acrylonitrile fiber, and then heating the fibers at a temperature of 80°C or higher for 5 to 180 minutes, preferably heating in a moist heat atmosphere at 100 to 150°C for 10 to 120 minutes.
[0023] The amount of carboxyl groups contained in the fiber hydrolyzed as described above is preferably 1.0 mmol / g as a lower limit, more preferably 1.5 mmol / g. If the amount of carboxyl groups is less than 1.0 mmol / g, there is a risk that satisfactory liquid absorption properties cannot be obtained. The upper limit is preferably 5.0 mmol / g, more preferably 4.0 mmol / g. If the amount of carboxyl groups is more than 5.0 mmol / g, there is a risk that the fiber properties are poor and handling is difficult.
[0024] The flatness of the absorbent sheath-core fiber when it is made into an absorbent transparent sheet, i.e., the ratio b / a of the long axis b to the short axis a of the fiber cross section, is preferably 1.10 as a lower limit, more preferably 1.40. If the flatness is less than 1.10, the transparency of the sheet may decrease, and it may be difficult to observe the state of the wound from the outside of the covering. Although the detailed mechanism of this is unclear, when the fiber cross section is flat, there are fewer voids inside the sheet compared to when the cross section is circular, and the frequency of light entering the sheet being refracted by air in the voids is also reduced, so that transparency is considered to be obtained. In addition, the upper limit is preferably 4.50, more preferably 2.30. If the flatness exceeds 4.50, the fiber physical properties may be deteriorated.
[0025] There is no particular limitation on the method for adjusting the flatness of such absorbent core-sheath fibers to the above-mentioned specified range, and any known method can be used, such as a method for obtaining flat fibers by a spinning process using a composite spinneret, or a method for producing a carded web and then heat-pressing it to deform the cross section of the fibers into a flat shape.
[0026] The fibers that can be mixed with the liquid-absorbent core-sheath fibers in the liquid-absorbent sheet of the present invention are not particularly limited, but from the standpoint of cost, it is preferable to use general-purpose fibers such as polyester, nylon, acrylic, polypropylene, polyethylene, vinylon, cotton, rayon, wool, and glass fibers.
[0027] The liquid-absorbent transparent sheet of the present invention has a swelling ratio (hereinafter referred to as liquid absorption ratio) when absorbing 0.9 wt% saline solution, preferably 1.8 times as a lower limit, more preferably 3.0 times. If the liquid absorption ratio is less than 1.8 times, when used as a wound dressing, it may not be able to absorb all the exudate, causing liquid leakage. The upper limit is preferably 15 times, more preferably 12 times. If the liquid absorption ratio exceeds 15 times, the gel strength during liquid absorption may decrease, and shape retention may be lost.
[0028] In addition, in the liquid-absorbent transparent sheet of the present invention, in the visibility test described below, the visibility both before and after liquid absorption is preferably 2 or more, and more preferably 3 or more. If the visibility is below 2, the transparency is insufficient, and it may be difficult to observe the wound from outside the covering.
[0029] In addition, when the above-mentioned absorbent sheath-core fibers are uniformly bonded while maintaining the fibrous state, the liquid-absorbent transparent sheet of the present invention can be thinned while maintaining the liquid-absorbency of the sheet. Here, "bonding" refers to a state in which the fibers are plastically deformed and bonded by pressure, and "uniformly bonded" refers to a state in which there are no parts that are not bonded and no parts that are clearly weakly bonded compared to other parts. From the viewpoint of plastic deformation, the bonding method is preferably thermocompression bonding in which pressure is applied under heat.
[0030] Although there is no particular limitation on the method for producing the liquid-absorbent sheet of the present invention described above, when preparing a sheet by the above-mentioned heat-pressing, examples include a method in which the above-mentioned liquid-absorbent sheath-core fibers or a blend of the fibers with other fibers is made into a spread web by a carding machine, and then the spread web is directly heat-pressed, or a method in which the spread web is passed through a needle punching process and then heat-pressed, etc. Here, from the viewpoint of uniform pressure bonding, it is preferable to use a smooth calendar roll or flat plate press machine for the heat pressing.
[0031] The lower limit of the heat press temperature is preferably 100°C, more preferably 120°C. If the heat press temperature is lower than 100°C, the density of the sheet may not increase, and the sheet may not be sufficiently thin. The upper limit is preferably 200°C, more preferably 180°C. If the heat press temperature exceeds 200°C, the physical properties of the fibers may decrease, and the physical properties and liquid absorption performance of the sheet may decrease, which is not preferable.
[0032] The pressure of the heat press is preferably 150 kgf / cm as a linear pressure, and more preferably 200 kgf / cm. If the pressure is less than 150 kgf / cm, the density of the sheet does not increase, and the thinning may be insufficient, which is not preferable. The upper limit is preferably 2500 kgf / cm, and more preferably 2300 kgf / cm. If the pressure is more than 2500 kgf / cm, the amount of liquid absorption and the liquid absorption speed may be slow, which is not preferable.
[0033] When the liquid-absorbent transparent sheet of the present invention is produced by the above-mentioned heat pressing, the liquid-absorbent sheath-core fibers exhibit their liquid-absorbing performance without being inhibited, even though the sheet is highly dense and thin. This is believed to be because, in the liquid-absorbent sheet of the present invention, the liquid-absorbent sheath-core fibers are merely pressed but are not fused and thus retain their fibrous state.
[0034] Although the reason why the fiber has the above-mentioned characteristics is unclear, it is believed that the acrylonitrile polymer contained in the fiber has a low glass transition point and softens at the heat press temperature, so that the fiber shape is not destroyed even during heat press and is deformed into a flat shape. Furthermore, since the acrylonitrile polymer does not melt, it is believed that each fiber maintains its independent state even after heat press.
[0035] The liquid-absorbent transparent sheet of the present invention has both excellent liquid absorption and transparency, and therefore can be suitably used as a wound dressing. In addition, one aspect of the effect of the present invention is that by adopting the liquid-absorbent core-sheath fiber, it is possible to form a sheet having sufficient strength without using a heat-fusible fiber, which is very advantageous in practical use.
[0036] Here, when the liquid-absorbent transparent sheet is used for the wound dressing, other materials may be combined in addition to the liquid-absorbent transparent sheet, and for example, when the liquid-absorbent transparent sheet and the gas-permeable film are laminated in this order from the side closest to the wound surface to form a wound dressing, the film prevents contamination from the outside such as bacteria and moisture, while evaporating the moisture absorbed by the liquid-absorbent sheet, thereby preventing excessive moisture from remaining inside the dressing. It is desirable that the gas-permeable film is transparent to such an extent that the transparency of the wound dressing as a whole is not impaired even before absorbing liquid, and examples of such films include silicone film and urethane film. EXAMPLES
[0037] The present invention will be described in detail below with reference to examples, but the scope of the present invention is not limited to these examples. Parts and percentages in the examples are by weight unless otherwise specified.
[0038] <Method of measuring liquid absorption capacity> Approximately 0.5 g of the sample sheet was immersed in 300 ml of 0.9% saline solution at 25°C for 30 minutes, and then centrifuged to dry (160G x 5 minutes, where G is the acceleration of gravity) to adjust the weight of the sample (Y1(g)). The sample was then dried in a vacuum dryer at 80°C until it reached a constant weight, after which the weight of the sample sheet (Y2(g)) was measured and the weight was calculated using the following formula. Absorption rate (times) = (Y1-Y2) / Y2
[0039] <Method for measuring the amount of carboxyl groups> After immersing the sample fiber in a sulfuric acid solution of pH 2-3 for 30 minutes, it is thoroughly washed with water and dried in a dryer at 80°C. After that, approximately 0.4 g of the sample fiber is weighed out (X1 (g)), which is placed in a solution of 0.5 g of sodium chloride dissolved in 100 ml of deionized water and stirred for 30 minutes. Next, 30 ml of 0.1 mol / L NaOH is dropped, and then several drops of phenolphthalein are dropped to confirm that the solution is colored red, and then the solution is stirred for another 30 minutes. After that, the sample fiber and the dispersion are separated using a wire mesh, and the dispersion is recovered. 0.1 mol / L HCl is dropped into the dispersion until the red color disappears (X2 (ml)). The amount of carboxyl groups is calculated according to the following formula. Carboxyl group amount (mmol / g) = (30-X2) x 0.1 / X1
[0040] <Method of measuring flatness> After cutting the sample sheet, a photograph of the cross section of the sheet was taken using an optical microscope, and the short axis (A) and long axis (B) of 50 fibers were measured from the photograph. B ) / ( A ) was calculated and the average was taken as the flatness.
[0041] <Method of measuring basis weight> A 10 cm x 10 cm test piece is taken from the sheet and dried at 105°C for 2 hours, after which the weight (W [g]) is measured and calculated using the following formula. Weight [g / m 2 ]=W / (0.1×0.1)
[0042] <Method of measuring sheet transparency (visibility)> A sample sheet measuring 5 cm x 7.5 cm was created from the sheet, and the sample sheet was placed on a gray copy paper printed with "RED" in red, "BLACK" in black, "WHITE" in white, and "YELLOW" in yellow (font: Mincho, size: 10.5P), and evaluated according to the following evaluation criteria. 1: I can't tell if there is writing on it, and I don't know what color it is. 2: I don't know what characters are written, or what color they are, but I can see the shades of color for each character. 3: I can't make out what words are written, and I can tell what color it is, but it looks blurred 4: The outlines of the letters are blurred, but you can tell what letters they are and what color they are. 5: Characters and colors are clearly visible Then, the sample sheet was placed in a transparent bag with a zipper, and 20 times the weight of the sample sheet was filled with 0.9% saline solution to allow the sample sheet to absorb the liquid. After absorbing the liquid, the sample sheet was placed on the copy paper while still in the transparent bag with a zipper, and evaluated according to the same criteria as above.
[0043] <Creating absorbent sheath-core fibers> A mixed aqueous solution of 35% sodium hydroxide and 0.1% hydrazine was applied to the surface of an acrylic fiber with a fineness of 3.3 dtex and a fiber length of 51 mm in an amount 1.5 times the weight of the acrylic fiber, and the fiber was hydrolyzed at 108°C for 15 minutes to create an absorbent core-sheath fiber (carboxyl group content 2.5 mmol / g) with an absorbent layer having salt-type carboxyl groups on the surface and a core-sheath structure with an acrylonitrile-based fiber part remaining in the center.
[0044] Example 1 The above-mentioned absorbent core-sheath fiber was used to make a carded fiber with a basis weight of 50 g / m 2 A spread web was prepared, and heat pressed using a smooth metal calendar roll at 150° C. and 198 kgf / cm to prepare a sheet of Example 1.
[0045] Example 2 A sheet of Example 2 was produced in the same manner as in Example 1, except that the pressing pressure was 264 kgf / cm.
[0046] Example 3 A sheet of Example 3 was produced in the same manner as in Example 1, except that the pressing pressure was 330 kgf / cm.
[0047] Example 4 A sheet of Example 4 was produced in the same manner as in Example 1, except that the pressing pressure was 1155 kgf / cm.
[0048] Example 5 A sheet of Example 5 was produced in the same manner as in Example 1, except that the pressing pressure was 2310 kgf / cm.
[0049] Example 6 The weight of the spread web is 25g / m 2 A sheet of Example 6 was prepared in the same manner as in Example 5 except for the above.
[0050] Example 7 The weight of the spread web is 100g / m 2 A sheet of Example 7 was produced in the same manner as in Example 5 except for the above.
[0051] Example 8 The sheet of Example 7 was produced in the same manner as in Example 4, except that a spread web was produced using 30% by weight of the aforementioned absorbent core-sheath fiber and 70% by weight of acrylic fiber K8 manufactured by Nippon Exlan Kogyo Co., Ltd.
[0052] Example 9 A sheet of Example 7 was produced in the same manner as in Example 4, except that a spread web was produced using 50% by weight of the aforementioned absorbent core-sheath fiber and 50% by weight of acrylic fiber K8 manufactured by Nippon Exlan Kogyo Co., Ltd.
[0053] Comparative Example 1 A sheet for Comparative Example 1 was produced in the same manner as in Example 1, except that no heat pressing was performed.
[0054] Comparative Example 2 The weight of the spread web is 200g / m 2 A sheet of Comparative Example 2 was prepared in the same manner as in Example 4 except for the above.
[0055] Table 1 shows the evaluation results for each of the examples and comparative examples.
[0056] [Table 1]
Claims
1. A liquid-absorbent transparent sheet comprising a liquid-absorbent sheath-core fiber composed of an outer layer containing a hydrophilic polymer and an inner layer containing an acrylonitrile-based polymer, the liquid-absorbent transparent sheet being characterized in that the flatness of the core-sheath fiber is 1.10 to 4.50, the basis weight of the liquid-absorbent transparent sheet is 25 to 180 g / m2, and the content of the core-sheath fiber in the liquid-absorbent transparent sheet is 25 to 100% by weight.
2. 2. The liquid-absorbent transparent sheet according to claim 1, wherein the liquid-absorbent transparent sheet has a liquid absorption ratio of 1.8 to 15 times.
3. A wound dressing comprising the liquid-absorbent transparent sheet according to claim 1 or 2.
4. 4. The wound dressing of claim 3, further comprising a breathable film.
5. 5. The wound dressing according to claim 4, wherein the breathable film is a urethane film or a silicone film.
Citation Information
Patent Citations
Laminate sheet-like structure
JP2021172014A
Water-swellable polymer gel and method for producing the same
JP4044291B2
